(940) Review on Research Activities Conducted at the Institute of National Planning Cairo with the Help of the Computer IBM 1620/940 مراجعة الأنشطة البحثية التي أجريت في معهد التخطيط القومي بالقاهرة بمساعدة جهاز الكمبيوتر ( الحاسوب ) آي بي إم 1620 - INP (The Institute of National Planning, 2024)
The utilization of computers in the preparation of national. development plans in U.AR. dates back to the early days of 1957 1.e. almost twelve years ago when the huge computers of today were still under the process of design and research. The necessity of seeking the help of computers, in the preparation of these plans, cale as a consequence of development of operational models at the sectoral level and hence at the comprehensive national level. These models bringing into existence the attractive idea of optimality appeared to be superior to classical techniques of planning based on sets of balances and target setting approach. For example the formulation of linear programming models for investment planning were initiated prior to the preparation of the 1st five years plan covering the years 1960-1965. Work on this field started in an experimental basis and was initiated by Prof. Dr. I. HELMI ABD-EL-RAHMAN Under Secretary of National Planning at that time and by Prof R. FRISCH who was leading the first group of Operations Research Specialists formulated in this country by the support of Dr.ABD-EL-RAHMAN at the National Planning of that time.